Preparation, Characterization and Biological Activity of New Nickel(II) Complexes Containing Mixed Ligands - Zuhoor Dawood; Adeeba Shareef (College of Education for Pure Sciences, 2007)
Nickel(II) complexes containing mixed ligands; semicarbazone (SCH) {benzaldehyde semicarbazone (BSCH) or 2-fluorobenzaldehyde semicarbazone (FSCH)} and salicylaldehyde (SH) or anthranilic acid (AH) or 2-  methylaminofuran (FH) have been prepared and characterized physicochemically. Complexes of the type [Ni(SCH)(LH)2](N03)2 {where SCH = BSCH or FSCH, LH = SH or AH or FH} have been proposed . The biological activities of the resulted complexes have been evaluated by agar plate diffution technique against five human pathogenic bacterial strains: Bacillus subtilis, Streptococcus pyogenes, Staphylococcus aureus, Pseudomonas aeruginosa and Proteus vulgaris. The complexes were found to have antimicrobial activity on some gram-positive and gram-negative bacteria, in vitro. The effective concentrations ranging between 31.25-500 J.lg/ml. Pseudomonas aeruginosa and Staphylococcus aureus were the most sensitive bacteria followed by Proteus vulgaris.